Niche Differentiation of Host-Associated Pelagic Microbes and Their Potential Contribution to Biogeochemical Cycling in Artificially Warmed Lakes - Samad, Md Sainur; Lee, Hyo Jung; Cerbin, Slawek; Meima-Franke, Marion; Bodelier, Paul L. E. (Frontiers in Microbiology, 2020)
It has been proposed that zooplankton-associated microbes provide numerous beneficial services to their “host”. However, there is still a lack of understanding concerning the effect of temperature on the zooplankton microbiome. Furthermore, it is unclear to what extent the zooplankton microbiome differs from free-living and phytoplankton-&-particle-associated (PPA) microbes. Here, we explicitly addressed these issues by investigating (1) the differences in free-living, PPA and zooplankton associated microbes; and (2) the impact of temperature on these microbes in the water column of a series of lakes artificially warmed by two power plants. High-throughput amplicon sequencing of the 16S rRNA gene showed that diversity and composition of the bacterial community associated to zooplankton, PPA, and bacterioplankton varied significantly from one another, grouping in different clusters indicating niche differentiation of pelagic microbes. From the abiotic parameters measured, temperature significantly affected the diversity and composition of all analysed microbiomes. Two phyla (e.g., Proteobacteria and Bacteroidetes) dominated in zooplankton microbiomes whereas Actinobacteria was the dominant phylum in the bacterioplankton. The microbial species richness and diversity was lower in zooplankton compared to bacterioplankton and PPA. Indicator species analysis showed that 9 %, 8 % 12 % and 21% unique OTUs were significantly associated with copepods, cladocerans, bacterioplankton, and PPA, respectively. Surprisingly, genera of methane oxidizing bacteria (MOB), methylotrophs and nitrifiers (e.g., Nitrobacter) significantly associated with the microbiome of zooplankton and PPA. Our study clearly demonstrates niche differentiation of pelagic microbes which is affected by warming with possible impact on biogeochemical cycling in freshwater systems.